Rice productivity variations in districts of Kelantan as affected by nutrient balance / Fathul Nabila Abd Karim - Abd Karim, Fathul Nabila (Faculty of Plantation and Agrotechnology, 2016)
Paddy yield is always affected by biotic and abiotic factors such as the soil fertility, the presence of pests and diseases and sufficient nutrients with the right proportions during growing period. The objectives of this study were to analyze the rice productivity in selected districts of Kelantan from the year of 2012 to 2014 and to relate productivity to crop nutrient assessment parameters obtained through the use of Diagnosis & Recommendations Integrated System (DRIS) approach. The method used secondary data (the yield of paddy and the crop nutrient analysis) obtained from the Department of Agriculture in Kelantan. The analyzed data was compared and evaluated with published data in the literature. In general, the result obtained from this study indicated that selected leaf nutrient ratio parameters in most crops in Kelantan did not exhibit nutrient ratios characterized by high yielding crops as established for rice crops in MADA. To conclude, there is a potential to increase yield of paddy in Kelantan if balanced fertilization is given during the entire cropping period.